CHALLENGES AND IMPLICATIONS OF THE SINGLE BAR SYSTEM ON LEGAL PROTECTION FOR ADVOCATES IN INDONESIA - Jevis, Weldy; Hosnah, Asmak; rohaedi, Edi (NOMOI Law Review, 2025)
The large number of advocates in Indonesia requires every advocate to be registered and joined in an association or organization. With the many advocate organizations in Indonesia, PERADI as an organization recognized by the state as a forum for advocate organizations to gather. PERADI is also a manifestation of the adoption of the single bar system in Indonesia. In the context of Indonesian law, advocate organizations must be registered with the Indonesian Advocates Association (PERADI) to obtain legal protection. However, many advocate organizations choose not to join Peradi, thus creating uncertainty regarding legal protection for their members. This study uses a normative juridical approach with a literature study to examine the legal norms governing the advocate profession, especially those related to the legal position of non-Peradi organizations, as well as the single bar system implemented in Indonesia. The research findings show that although non-Peradi organizations have temporary authority to carry out certain functions, their legal status is still ambiguous and affects the legal protection provided to their members. In addition, the implementation of the single bar system in Indonesia provides advantages in terms of supervision and professional development, but also faces major challenges in terms of accessibility of advocates in remote areas to services provided by PERADI.